Antiparasitic activity of the iron-containing milk protein lactoferrin and its potential derivatives against human intestinal and blood parasites - Anand, Namrata (Frontiers in Parasitology, 2024)
An iron-containing milk protein named lactoferrin (Lf) has demonstrated antiparasitic and immunomodulatory properties against a variety of human parasites. This protein has shown its capability to bind and transport iron molecules in the vicinity of the host–pathogen environment. The ability of parasites to sequester the iron molecule and to increase their pathogenicity and survival depends on the availability of iron sources. Lf protein has suggested a iron chelating effect on parasites iron and, hence, has shown its antiparasitic effect. Since the parasites have a complex life cycle and have developed drug resistance, vaccines and other treatments are a handful. Therefore, therapeutic research focusing on natural treatment regimens that target the parasite and are non-toxic to host cells is urgently needed. The antiparasitic efficacy of Lf protein has been extensively studied over the past 40 years using both in vitro and in vivo studies. This review article highlighted past important studies on Lf protein that revealed its potential antiparasitic activity against various intracellular and extracellular intestinal or blood-borne human parasites. This review article structures the role of Lf protein in its various forms, such as native, peptide, and nanoformulation, laying the groundwork for its function as an antiparasitic agent and its possible known mechanisms of action.